2010
DOI: 10.1111/j.1443-1661.2010.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Outcome of Endoscopic Papillotomy for Choledocholithiasis With Cholecystolithiasis

Abstract: Pneumobilia was the only significant risk factor for cholecystitis and recurrent choledocholithiasis in our study population. As for the long-term outcome, it was unclear whether endoscopic papillotomy contributed to the occurrence of biliary tract cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
1
32
0
2
Order By: Relevance
“…Some authors have identified bile duct size >15 mm as a risk factor for recurrent stones 18,21,32. A dilated CBD is likely to lead to bile stasis and bacterial infection, which play central roles in the mechanism of stone formation 20,24,33. There are some possibilities of small fragmented stones missed by cholangiogram in patients with a large bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have identified bile duct size >15 mm as a risk factor for recurrent stones 18,21,32. A dilated CBD is likely to lead to bile stasis and bacterial infection, which play central roles in the mechanism of stone formation 20,24,33. There are some possibilities of small fragmented stones missed by cholangiogram in patients with a large bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…However, as deaths from causes unrelated to gallstones were included, there may have been selection bias related to patient variables. A post-EST cohort study found that pneumobilia increased the risk of complications in gallbladder-preserved cases, but no data on the risk of death were shown [165,166]. Although not removing the gallbladder after EST is clearly associated with gallstonerelated complications in the long term, it remains unknown whether this is associated with increased mortality.…”
Section: Commentarymentioning
confidence: 99%
“…Also, the long-term outcome of EST has been of concern 9,10. Fujimoto et al 11. followed up 522 patients who received EST due to choledocholithiasis and cholelithiasis for 5.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of comparative studies are controversial 5,6. Furthermore, EST causes early and late complications, such as pancreatitis, perforation, bleeding, permanent loss of sphincter Oddi function, bacterial translocation in the bile duct, and recurrence of biliary colic 711…”
Section: Introductionmentioning
confidence: 99%